2019
DOI: 10.1002/jnm.2644
|View full text |Cite
|
Sign up to set email alerts
|

Millimeter wave balun design and optimization based on compensation matching capacitors and active S parameter

Abstract: A balun design algorithm based on the compensation matching capacitors and the active S parameter is given in this paper. Compared with the inductor matching network, the compensation matching capacitors not only compensate the phase and the amplitude error of the balun, but also occupy a compact chip area. Considering the coupling between two differential terminals of the balun, the active S parameter is adopted. On the basis of the active S parameter, the reflection coefficients of two differential terminals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…All RF components are designed in differential structures for robust RF performance, except the power combiner and switches. The input and output baluns are realized by octangular fashions for high quality factor [ 26, 27 ] . All the states of the phase shifter and attenuator are set by an on‐chip standard serial peripheral interface (SPI) controller.…”
Section: System Analysismentioning
confidence: 99%
“…All RF components are designed in differential structures for robust RF performance, except the power combiner and switches. The input and output baluns are realized by octangular fashions for high quality factor [ 26, 27 ] . All the states of the phase shifter and attenuator are set by an on‐chip standard serial peripheral interface (SPI) controller.…”
Section: System Analysismentioning
confidence: 99%
“…Zhang et al presented an improved wideband single‐π model for on‐chip spiral inductors based on independent test ground PADs. A different group by Zhang et al reported a balun design algorithm based on compensation matching capacitors and their active S parameters. Using CMOS technology, Chen et al designed a millimeter‐wave up‐conversion mixer by using a two‐path transconductance stage and Yu et al reported a linear V‐band low‐noise amplifier by employing a Gm‐boosting technique using full‐wave high‐frequency structure simulator.…”
mentioning
confidence: 99%